What Did You Mean? - Facing the Challenges of User-generated Software Requirements - Geierhos, Michaela; Schulze, Sabine; Bäumer, Frederik (Proceedings of the International Conference on Agents and Artificial Intelligence)
Existing approaches towards service composition demand requirements of the customers in terms of service templates, service query profiles, or partial process models. However, addressed non-expert customers may be unable to fill-in the slots of service templates as requested or to describe, for example, pre- and postconditions, or even have difficulties in formalizing their requirements. Thus, our idea is to provide non-experts with suggestions how to complete or clarify their requirement descriptions written in natural language. Two main issues have to be tackled: (1) partial or full inability (incapacity) of non-experts to specify their requirements correctly in formal and precise ways, and (2) problems in text analysis due to fuzziness in natural language. We present ideas how to face these challenges by means of requirement disambiguation and completion. Therefore, we conduct ontology-based requirement extraction and similarity retrieval based on requirement descriptions that are gathered from App marketplaces. The innovative aspect of our work is that we support users without expert knowledge in writing their requirements by simultaneously resolving ambiguity, vagueness, and underspecification in natural language
Keywords: User-generated Natural Language Requirements; Interactive Requirement Disambiguation and Completion